Development of a competence ecosystem for the future space workforce: strategies, practices and recommendations from international master programs in northern Sweden. (August 2022) - Barabash, Victoria; Milz, Mathias; Kuhn, Thomas; Laufer, Rene
Abstract: Requirements from the global labor market have substantially changed in recent years. Graduate and post-graduate students with excellent subject knowledge, deep understanding of modern working methods, technical and higher-order thinking, engineering intuition and problem-solving skills are in great demand. They should also have professional skills such as well-developed abilities in communication and teamwork, usually in an international work environment. This review discusses the advantages of multidisciplinary study environment, educational strategies such as student-oriented teaching, project-based learning with its applicability to a "real-world" setting, active learning techniques, development of entrepreneurial skills, lessons learned and best practices from the international Master Program in Spacecraft Design and the Joint Master Program in Space Science and Technology – SpaceMaster at Luleå University of Technology in northern Sweden. The importance of complementarity between formal, informal and non-formal learning methods for science and engineering students has been specifically highlighted. Connections to the world of work, through active industry involvement in the education in a systematic way, e.g. External Advisory Board, shared services and facilities, joint projects and supervision of Master and PhD students, is recognised as a key success factor for professional training. A structural combination of modern pedagogical tools, strategic partnership with industry, business entities, academic partners and up-to-date multidisciplinary labs creates the conceptual framework for a Competence Ecosystem for fostering a new generation of space scientists and engineers. Highlights: New professional skills for the modern space sector . Successful educational strategies and best practices from the international Master programs in space science and technology. Competence ecosystem as an effective tool for fostering of new competences and addressing the New Space agenda.